CONCEPT OF GLOBAL HEALTH DIPLOMACY IN INTERNATIONAL RELATIONS - Laode Muhamad Fathun; Nurmasari Situmeang (AEGIS : Journal of International Relations, 2021)
This paper's purpose is to explain describes the correlation of the spread of the Covid19 virus as a global problem. The spread will form a global health diplomacy collaboration to tackle Covid19 massive spread that makes countries overwhelmed to overcome it. This paper is used for library research to research methodology with qualitative descriptive analysis paradigm. This paper result to finds that to overcome these problems, each country must interpret that international mismarked security is more important than the political and economic interests of the country. That means that cooperation must be interpreted that the Covid19 outbreak is a global problem, must be handled by multiple stakeholders, long term, and cooperation based on the nature of extremism. With the ready ness negotiation method. This interpretation is expected to be an inclusive way to be able to respond to cooperation that understands, shares, and enjoys together with global health diplomacy as to develop international governance cooperation with altruism model and ready ness negotiation.